2018
DOI: 10.1007/s10068-018-0437-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of green tea contents on the quality and antioxidant properties of textured vegetable protein by extrusion-cooking

Abstract: The aim of this study was to evaluate the effects of green tea contents (0, 5, 10, and 15%) on texturization and antioxidant properties of textured vegetable protein (TVP) by using a twin-screw extruder. Extrusion conditions were fixed at 140°C barrel temperature, 50% moisture content, 100 g/min feed rate, and 200 rpm screw speed. The integrity index, hardness, and cutting strength of TVP significantly (P \ 0.05) increased with the increase in green tea levels, while cohesiveness, springiness, water holding ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…In the present study, oyster mushroom was added into the feed mixture because of its rich source of dietary fiber and protein [ 11 , 13 ]. Recent studies reported that a decrease in extrudate expansion increases the fiber and protein contents in the development of textured vegetable protein [ 4 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, oyster mushroom was added into the feed mixture because of its rich source of dietary fiber and protein [ 11 , 13 ]. Recent studies reported that a decrease in extrudate expansion increases the fiber and protein contents in the development of textured vegetable protein [ 4 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…The TI was dependent on the extruder parameters (e.g., type of extruder, screw configuration, rotation speed, barrel temperatures, and feed rate) and feed conditions (e.g., ingredients and moisture content) applied. Numerous studies have investigated the effect of these independent variables on the TI of soy protein-based meat analogs [ 10 , 22 , 23 , 30 , 31 , 32 ]. The TI of the oyster mushroom-soy protein meat analogs ranged from 0.77 to 1.19 ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the breaking strength of DGTN was high, its flexibility would become worse. Previous studies found that cutting strength of textured vegetable protein with high GTP level increased owing to high density and hard extrudate, and appropriate GTP level improved microstructure of textured vegetable protein more orderly [25]. Therefore, textural property changes of DGTN with different particle sizes and concentrations of GTP would probably be attributed to the microstructure of DGTN.…”
Section: Texture Properties Of Dgtnmentioning
confidence: 92%
“…To increase consumer acceptability of extruded snacks containing mushroom, flavor addition to the extruded snacks will be evaluated in the future. There have been various studies evaluating quality of extruded products processed under a constant barrel temperature (Ma & Ryu, ; Sayanjali et al, ; Sumargo et al, ). However, barrel temperatures have been shown to affect quality of extrudates (Wan et al, ).…”
Section: Resultsmentioning
confidence: 99%